2019
DOI: 10.1016/j.stemcr.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Chromatin and 3D Genome Architecture Changes from Naive to Primed Human Embryonic Stem Cell States

Abstract: Summary During mammalian embryogenesis, changes in morphology and gene expression are concurrent with epigenomic reprogramming. Using human embryonic stem cells representing the preimplantation blastocyst (naive) and postimplantation epiblast (primed), our data in 2iL/I/F naive cells demonstrate that a substantial portion of known human enhancers are premarked by H3K4me1, providing an enhanced open chromatin state in naive pluripotency. The 2iL/I/F enhancer repertoire occupies 9% of the genome, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 63 publications
5
20
2
Order By: Relevance
“…Similarly, we detected a decrease of H3K9Me3 in the naive state, although it was not significant. In contrast to our results however, previous studies using regular ChIP-Seq have reported higher levels of H3K27Me3 in primed hESCs, compared to naive hESCs 20,21,41,42 . Notably, it has been shown that quantitative analysis of ChIP-Seq signals require the use of a spike-in for proper normalization 31 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, we detected a decrease of H3K9Me3 in the naive state, although it was not significant. In contrast to our results however, previous studies using regular ChIP-Seq have reported higher levels of H3K27Me3 in primed hESCs, compared to naive hESCs 20,21,41,42 . Notably, it has been shown that quantitative analysis of ChIP-Seq signals require the use of a spike-in for proper normalization 31 .…”
Section: Discussioncontrasting
confidence: 99%
“…The H3K4 peptides are poorly recovered by bottom-up MS because they are not well retained on C18 liquid chromatography colums 40 . The H3K9Me3 mark was shown to be depleted in naive cells and cells transitioning towards the primed state 20,41,42 . Similarly, we detected a decrease of H3K9Me3 in the naive state, although it was not significant.…”
Section: Discussionmentioning
confidence: 98%
“…The high-level structural organisation of TADs and spatial compartments was similar between pluripotent states, which is in agreement with recent previous reports in these and other cell types (Battle et al, 2019;Dixon et al, 2015;Ji et al, 2016). Within those topological features, however, interaction subnetworks that are formed of large, highly connected hubs changed substantially in their interaction frequency and, for a subset, also in their transcriptional activity between pluripotent states.…”
Section: Discussionsupporting
confidence: 91%
“…Within individual primed cells, these lineage-specifying gene expression programs are in competition with each-other, and they are also moderately expressed and not fully established. Indeed, there is evidence that nascent germ layer programs rely on relatively weak enhancers which are not yet fully established [ 70 , 82 , 114 , 115 ], while the naïve enhancers retain a capacity to rapidly return to full strength, retaining their plasticity [ 10 ]. Thus, upon global hyperactivation of enhancers by 2i or CDK8/19i, the naïve program becomes dominant, quickly suppressing forward differentiation of the nascent germ layer programs ( Fig.…”
Section: Model: Dominant Programs Resolve Transcriptional Decisions Imentioning
confidence: 99%